2021
DOI: 10.1021/acsomega.1c05132
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Production Prediction Model Based on a Stacked LSTM Network and Transfer Learning

Abstract: Gas injection and water injection are common and effective methods to improve oil recovery. To ensure its production effect, it is necessary to simulate the oilfield production process. However, traditional composition simulation runs a large number of calculations and takes a long time. Through the analysis of relevant data, we found that production is affected by many factors and has a strong sequential character. Therefore, this paper proposes a deep learning model for reservoir production prediction based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Its transmission from input state to the hidden state uses the matrix multiplication of the fully connected layer, and the feature state is transferred in the time dimension. A convolutional neural network performs better in dealing with grid data with spatial correlation [21]. ConvLSTM [12] replaces the full connection layer in LSTM units with a convolution layer, which solves the problem that traditional LSTM cannot describe spatial structure to a certain extent.…”
Section: Architecture Of Ctrl-clstmmentioning
confidence: 99%
“…Its transmission from input state to the hidden state uses the matrix multiplication of the fully connected layer, and the feature state is transferred in the time dimension. A convolutional neural network performs better in dealing with grid data with spatial correlation [21]. ConvLSTM [12] replaces the full connection layer in LSTM units with a convolution layer, which solves the problem that traditional LSTM cannot describe spatial structure to a certain extent.…”
Section: Architecture Of Ctrl-clstmmentioning
confidence: 99%
“…The generation of the steam temperature has a significant delay characteristic. The long short-term memory network (LSTM) has good performance in time-series forecasting, which solves the problems of gradient disappearance, gradient explosion, and a long sequence dependence in the long sequence training process. , Gupta et al used a single layer of LSTM with 32 nodes to predict fouling in air preheaters, which can be predicted 3 months in advance. Tan et al analyzed the effect of different delay time sequences on the model.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a long training time, low prediction accuracy, and overfitting in the prediction process . The LSTM neural network model in deep learning has high prediction accuracy and can effectively overcome the problems of overfitting in previous methods. , This method is also suitable for predicting the ROP of other oilfields …”
Section: Introductionmentioning
confidence: 99%
“…31 The LSTM neural network model in deep learning has high prediction accuracy and can effectively overcome the problems of overfitting in previous methods. 32,33 This method is also suitable for predicting the ROP of other oilfields. 3 Previous research works also confirmed the efficiency of using the PSO algorithm and LSTM neural networks in solving complex engineering problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation